2022
DOI: 10.3389/fpsyg.2022.940138
|View full text |Cite
|
Sign up to set email alerts
|

The impact of implicit theories on resilience among Chinese nurses: The chain mediating effect of grit and meaning in life

Abstract: Implicit theories refer to assumptions people hold about different domains, also known as mindsets. There are two implicit theories on the malleability of one’s ability: entity theory and incremental theory. They constrain and regulate people’s understanding and responses to an individual’s behavior, leading to different social cognitive patterns and behavioral responses. Resilience is a positive adaptation in highly stressful situations that represents mechanisms for coping with and transcending difficult exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The theory on the relationship between grit and health ( Kobasa and Puccetti, 1983 ) holds that grit is a protective factor for people dealing with stressful events. Grit is negatively related to negative emotions ( Clement et al, 2020 ; Lee M., 2022 ), and individuals who persevere tend to have more positive emotions ( Lee M., 2022 ), stronger psychological resilience ( Tang et al, 2022 ), are more likely to receive social support, and have a higher level of hope ( Yang and Wu, 2021 ). Nurses with low grit have been found to have higher stress levels and more mental health problems, such as anxiety, depression, and other harmful emotions ( Peng and Wu, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The theory on the relationship between grit and health ( Kobasa and Puccetti, 1983 ) holds that grit is a protective factor for people dealing with stressful events. Grit is negatively related to negative emotions ( Clement et al, 2020 ; Lee M., 2022 ), and individuals who persevere tend to have more positive emotions ( Lee M., 2022 ), stronger psychological resilience ( Tang et al, 2022 ), are more likely to receive social support, and have a higher level of hope ( Yang and Wu, 2021 ). Nurses with low grit have been found to have higher stress levels and more mental health problems, such as anxiety, depression, and other harmful emotions ( Peng and Wu, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Yıldırım et al [48] found that individuals with a high meaning in life were more resilient when faced with setbacks or trauma. Tang et al [49] reported that a meaningful life could be a protective factor that enhances resilience in nurses. Therefore, resilience and meaning in life were positively correlated in both directions.…”
Section: Discussionmentioning
confidence: 99%